Child psychology pathways to good practice - Pote, Helen; Picciotto, Anna; Norris, Clare
This comprehensive text on child psychology is edited by Helen Pote, Anna Picciotto, and Clare Norris. It provides an extensive overview of the frameworks and practices in the field of child psychology, particularly within the UK NHS context. The book is designed for both novice and experienced practitioners, offering guidance on developing clinical confidence, understanding the political and societal influences on service delivery, and adopting a developmental approach to assessment and formulation. Key topics include inclusivity, diversity, supervision, and collaboration, with practical applications across various contexts such as schools, healthcare, and social care. The book aims to equip practitioners with the skills to effectively communicate psychological ideas and support the mental health and wellbeing of children and young people.